The efficiency of chlorophyll fluorescence as a selection criterion for salinity and climate aridity tolerance in barley genotypes - Hammami, Zied; Tounsi-Hammami, Soumaya; Nhamo, Nhamo; Rezgui, Saleh; Trifa, Yousef (Frontiers in Plant Science, 2024)
In the Near East and North Africa (NENA) region, crop production is being affected by various abiotic factors, including freshwater scarcity, climate, and soil salinity. As a result, farmers in this region are in search of salt-tolerant crops that can thrive in these harsh environments, using poor-quality groundwater. The main staple food crop for most of the countries in this region, Tunisia included, is barley.The present study was designed to investigate the sensitivity and tolerance of six distinct barley genotypes to aridity and salinity stresses in five different natural field environments by measuring their photosynthetic activity. The results revealed that tolerant genotypes were significantly less affected by these stress factors than sensitive genotypes. The genotypes that were more susceptible to salinity and aridity stress exhibited a significant decline in their photosynthetic activity. Additionally, the fluorescence yields in growth phases J, I, and P declined significantly in the order of humid environment (BEJ), semi-arid site (KAI), and arid environment (MED) and became more significant when salt stress was added through the use of saline water for irrigation. The stress adversely affected the quantum yield of primary photochemistry (φP0), the quantum yield of electron transport (φE0), and the efficiency by trapped excitation (ѱ0) in the vulnerable barley genotypes. Moreover, the performance index (PI) of the photosystem II (PSII) was found to be the most distinguishing parameter among the genotypes tested. The PI of sensitive genotypes was adversely affected by aridity and salinity. The PI of ICARDA20 and Konouz decreased by approximately 18% and 33%, respectively, when irrigated with non-saline water. The reduction was even greater, reaching 39%, for both genotypes when irrigated with saline water. However, tolerant genotypes Souihli and Batini 100/1B were less impacted by these stress factors. The fluorescence study provided insights into the photosynthetic apparatus of barley genotypes under stress. It enabled reliable salinity tolerance screening. Furthermore, the study confirmed that the chlorophyll a fluorescence induction curve had an inflection point (step K) even before the onset of visible signs of stress, indicating physiological disturbances, making chlorophyll fluorescence an effective tool for identifying salinity tolerance in barley.